The self-study of teaching practice and students’ assessment of the teacher - The, Hery Yanto; Latifah, Latifah (Cendikia : Media Jurnal Ilmiah Pendidikan, 2024)
Evaluation of teaching practice is often conducted by the university assessment board through a single instance of seeing a class through a walk-through observation. Oftentimes, teachers would receive either positive or unintelligible comments from the evaluation board. Ultimately, teachers must gather information from several sources, including peer criticism, reflection on educational theories or practices, self-assessment, and students' appraisals of instruction, to make changes to their lessons and teaching tactics. During this self-study, we examined and analyzed students' assessments of the teacher from the viewpoint of a critical friend. A total of 262 Chinese students enrolled in the English Speaking I course participated in the end-of-semester evaluation. We gathered data with a semi-structured questionnaire through the Zoho Survey platform. The data were subsequently examined using descriptive statistics and critical friend feedback. The teacher received both commendation and criticism in the evaluation. By carefully reflecting on the successful implementation, the teacher can use critical feedback from a trusted colleague to plan and develop alternate strategies to address any areas that need improvement in their teaching techniques.